2020
DOI: 10.1093/cid/ciaa1814
|View full text |Cite
|
Sign up to set email alerts
|

Assessment and Simplification of Treatment Eligibility Among Patients With Chronic Hepatitis B Infection in Vietnam

Abstract: Background Treatment eligibility and the accuracy of its simplified criteria have been poorly documented in patients with chronic HBV infection worldwide, especially in low-and-middle-income countries. Methods From a cohort of HBV-infected patients in Vietnam, we assessed the proportion of patients eligible for treatment using the national guidelines based on reference tests (HBV DNA quantification and FibroScan); and the acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 27 publications
1
7
1
Order By: Relevance
“…A multicenter study in Australia revealed that TREAT-B had greater sensitivity (91%) but lesser specificity (63%) in the hospital than in the community cohort (sensitivity, 70%; specificity, 88%) ( 18 ). TREAT-B of ≥2 demonstrated a sensitivity of 94.6% and specificity of 46.7% in a cohort of Vietnamese patients with chronic HBV ( 14 ), a finding consistent with this current study showing that using a cut-off of TREAT-B of ≥2 had excellent sensitivity (96.3%) but low specificity (41.4%) and fair accuracy (AUROC, 0.69; 95% CI, 0.58–0.66). Therefore, using the cut-off of ≥2, 59.6% of patients receiving antiviral would have been unnecessary.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…A multicenter study in Australia revealed that TREAT-B had greater sensitivity (91%) but lesser specificity (63%) in the hospital than in the community cohort (sensitivity, 70%; specificity, 88%) ( 18 ). TREAT-B of ≥2 demonstrated a sensitivity of 94.6% and specificity of 46.7% in a cohort of Vietnamese patients with chronic HBV ( 14 ), a finding consistent with this current study showing that using a cut-off of TREAT-B of ≥2 had excellent sensitivity (96.3%) but low specificity (41.4%) and fair accuracy (AUROC, 0.69; 95% CI, 0.58–0.66). Therefore, using the cut-off of ≥2, 59.6% of patients receiving antiviral would have been unnecessary.…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies found inconsistent results about the influence of using point-of-care HBeAg testing on the performance of TREAT-B for determining HBV treatment eligibility. A Vietnamese cohort showed that TREAT-B was accurate when a rapid HBeAg test (SD Bioline, South Korea) was used ( 14 ). In contrast, a Malawian cohort found that three commercial HBeAg rapid diagnostic tests, including SD Bioline (Gauteng, South Africa), Creative Diagnostics (Shirley, NY, USA), and Biopanda Reagents (Belfast, UK) had insufficient sensitivity, potentially rejecting patients access to treatment based on TREAT-B score ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Racial differences were also apparent in performance studies of the WHO simplified criteria and the TREAT-B scoring system conducted among African, European, Australian, and Vietnamese populations. The sensitivities of the WHO criteria and the TREAT-B scoring system for chronic hepatitis B treatment eligibility ranged between 53.0% and 100.0% and from 73.9% to 98.8% [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ], respectively. Similarly, the specificity ranges of the WHO criteria and TREAT-B system for chronic hepatitis B treatment eligibility were from 40% to 77.4% and 57.5% to 88.0 [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ], respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The WHO’s simplified criteria and the TREAT-B scoring system were validated in African, European, Australian, and Vietnamese populations. They showed variations in performance across geographic areas [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. The variations were explained by differences in viral genotype, modes of HBV transmission, and rates of spontaneous loss of HBeAg [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%